Improvement Of CEFR Levels in Foreign Language Teaching (Journal of Pedagogical Inventions and Practices, 2024)
The article "Improvement of CEFR Levels in Foreign Language Teaching" explores the efficacy of incorporating the Common European Framework of Reference for Languages (CEFR) in foreign language instruction to enhance language learning outcomes. The article provides an overview of the CEFR and its relevance in language education, emphasizing its role in setting clear learning objectives, assessing proficiency levels, and promoting international language standards